Integrating Faith and Consumer Ethics: A Study of Islamic Economics Students’ Consumption Behavior - Royhan Maliki Rizqi (Multidisciplinary Journal of Contemporary Islamic Discourse, 2026)
Consumption behavior is an essential aspect of daily human life and a key focus within microeconomic analysis. In Islamic economics, consumption is not merely about fulfilling desires but is guided by a hierarchy of needs: dharuriyat (essentials), hajiyat (complementary needs), and tahsiniyat (luxuries). Unlike conventional economic perspectives, Islam integrates faith and consumption, emphasizing that belief (iman) plays a significant role in shaping individual behavior and worldview. This research, conducted by Royhan Maliki Rizqi, is titled "Analysis of Consumption Behavior of Islamic Economics Students at UIN Walisongo Semarang from the Perspective of Islamic Economics." The study aims to explore how students of the Islamic Economics Department understand and practice consumer behavior aligned with the core principles of Islamic economics. The research adopts a qualitative approach using library research methods to analyze relevant texts and sources. The novelty of this study lies in its focus on a specific demographic—students who are expected to have theoretical knowledge of Islamic economic values—and examines the extent to which these values influence their actual consumption patterns. The findings reveal that while students have a conceptual understanding of Islamic consumption ethics, practical implementation often varies due to modern lifestyle influences and socio-economic factors. The study implies that educational institutions should strengthen the integration of Islamic ethical teachings in daily economic behavior to foster a more value-based consumer mindset. This research contributes to the broader discourse on aligning faith and economic practice, particularly in shaping future Muslim economic professionals.